A case study on the Six Sigma - away forward to future strategy toward continuous improvement in consultancy firm / Agatha Ajeng - Ajeng, Agatha (Faculty of Business and Management, 2009)
Understanding the six sigma strategy, challengers / obstacles and benefits allow organization to better support their strategic direction, and increasing need for monitoring and training. It’s also provides opportunity to better implement six sigma projects. This paper identifies the gap and the key factors that influencing six sigma project implementations. Effective six sigma principles and practices will succeed by refining the organizational culture continuously. Cultural changes require time and commitment before they are strongly implanted into organization. So this paper is more to prove does the strategy really help the company to achieve their objectives and goal and also does the company really implement the strategy in their company. In order to make this clear and to prove it was worth for the company to implement it in the company, the researcher decide to prove it by using the company cash flow for before and after the implementation of the strategy in the company. The reason for the researcher chooses a cash flow as a method to make a comparison is because of the characteristic of the cash itself which is most liquidity asset in the company and the cash flow also shows the healthy of the company. After analyze the company cash flow for before and after the implementation, the researcher find out there are positive changes in the company cash flow which is their cash flow was increase dramatically. So, this shows and proves that it was worth for the company to implement the strategy in the company. As a recommendation, the company should have a continuous training for their staff in order to make sure everyone in the company understand the strategy and how it work in the company it is because all the people in the company is responsibilities for the company quality improvement. To sustain and continuously improve, an organization needs to develop its people. Six Sigma also need the top management dedication and contribution to resources and effort in order to make sure this strategy fully implemented in the company.